Shifting the Paradigm: A Constructivist Analysis of Agency and Structure in Sustained Youth Sport Participation - Flaherty, Meredith; Sagas, Michael (Frontiers in Psychology, 2021)
To examine the impact of the relationship between agency and structure on sustained participation in youth sport, semi-structured interviews were conducted with male college soccer players. The participants’ accounts (N=20) of their youth careers were analyzed through the lens of Structuration Theory (ST) framed in a constructivist paradigm. ST supports the significance of the recursive relationship between agent and structure in-context in the co-construction of experiences, and provides a framework for analyzing effects of compounding experiences gained across time and space as they influence sport continuation. Clarity of expectations imposed in-context and the athlete’s perceived impact on the structure evidenced, through deductive thematic analysis, as the most salient determinants of the perceived valence of the youth sport environment. The agent’s perceived holding of authoritative resources across time and contexts was a critical dimension of the participants’ continuation in youth sport, substantiating ST as a theoretical lens, situated in a constructivist paradigm, that might add depth to understanding patterns in participation and attrition.